A classroom experiment in monetary policy. Issue 2 (3rd April 2019) - Duffy, John; Jenkins, Brian C.
Abstract: The authors propose a classroom experiment implementing a simple version of a New Keynesian model suitable for courses in intermediate macroeconomics and money and banking. Students play as either the central bank or members of the private sector. The central banker sets interest rates to meet twin objectives for inflation and the output gap or to meet only an inflation target. In both settings, private sector agents are concerned with correctly forecasting the inflation rate. The authors show that an experiment implementing this setup is feasible and yields results that enhance understanding of the New Keynesian model of monetary policy. They propose alternative versions where the central bank is replaced by a policy rule and provide suggestions for discussing the experimental results with students.